Observations for Construction and Validation of Research - Tarazona Mirabal, Herman (2020)
Design of a measurement instrument is a multidisciplinary task. To measure some trait without major implications - depending on the application you are given- it will be needed specialists in construct, statistical analysts, test designers, and language specialists. In fact, specialized knowledge is required for the design or adaptation of instruments that have broad repercussions, such as, validating a medical diagnostic instrument. Metric characteristics of an instrument are its validity and reliability. Validity refers to the accuracy of physical instruments and the reliability of measurement precision. In addition, validities that are representative of this characteristic are content, construct and criterion validity, while reliability of the instrument increases when errors are identified and these can be controlled.